A Proteome Quality Index. (22nd October 2014) - Zaucha, Jan; Stahlhacke, Jonathan; Oates, Matt E.; Thurlby, Natalie; Rackham, Owen J. L.; Fang, Hai; Smithers, Ben; Gough, Julian
Summary We present the Proteome Quality Index (PQI; http://pqi‐list.org), a much‐needed resource for users of bacterial and eukaryotic proteomes. Completely sequenced genomes for which there is an available set of protein sequences (the proteome) are given a one‐ to five‐star rating supported by 11 different metrics of quality. The database indexes over 3000 proteomes at the time of writing and is provided via a website for browsing, filtering and downloading. Previous to this work, there was no systematic way to account for the large variability in quality of the thousands of proteomes, and this is likely to have profoundly influenced the outcome of many published studies, in particular large‐scale comparative analyses. The lack of a measure of proteome quality is likely due to the difficulty in producing one, a problem that we have approached by integrating multiple metrics. The continued development and improvement of the index will require the contribution of additional metrics by us and by others; the PQI provides a useful point of reference for the scientific community, but it is only the first step towards a 'standard' for the field.